Redefining Teacher Leadership in the Age of ChatGPT: Instructional Practices, Ethical Challenges, and Professional Agency in Moroccan High Schools - ELFIRAOUI, WIDAD; Farhane, Hamza; Zakhir, Marouane (International Journal of Language and Literary Studies, 2026)
The integration of generative artificial intelligence (AI) tools such as ChatGPT is increasingly influencing teaching and learning in Moroccan secondary schools. This study investigates how high school teachers use ChatGPT in lesson design, activity creation, and feedback, and how such practices are redefining teacher leadership within the classroom. Anchored in the framework of instructional leadership, the study explores the opportunities and challenges faced by Moroccan teachers as they negotiate the balance between AI support and professional judgment. A mixed-methods design was adopted. Quantitative data were gathered from a survey of 87 Moroccan high school teachers working in the Casablanca-Settat region, while qualitative data were collected through semi-structured interviews with 12 teachers and analysis of lesson plans developed with ChatGPT. Descriptive statistics revealed that 64% of teachers reported using ChatGPT for lesson planning, 52% for activity generation, and 41% for drafting feedback. Qualitative findings highlighted three dominant themes: (1) pedagogical efficiency and creativity, with teachers noting time-saving benefits and new activity ideas, (2) ethical and pedagogical concerns, including fears of plagiarism, student overreliance, and occasional inaccuracies, and (3) leadership and professional agency, where teachers positioned themselves as guides who critically filter ChatGPT outputs and model responsible AI use for students. The study concludes that ChatGPT is not replacing teachers but is reshaping their leadership roles as instructional leaders, decision-makers, and ethical mediators in the classroom. These findings underscore the need for professional development programs on AI literacy and for policy guidelines that address responsible AI integration in Moroccan high schools.